Evaluation of Cooperation Strategy in Financial Services Supply Chain Based on Prospect Theory and Game Theory - Mohammad Shahab Rezvani; Hannan Amoozad Mahdiraji; Ezatollah Abbasian; Mohammadreza Mehregan (Iranian Journal of Accounting, Auditing & Finance, 2023)
Based on the prospect theory, the current research evaluated the cooperation strategy in the financial services supply chain. This research was descriptive in data collection and quantitative in terms of method. The game theory approach in this research was modeled using the Stackelberg approach. Cooperation strategies in the supply chain included reducing sensitivity, expanding profits, avoiding losses, and relying on references. The 4-player game was used to achieve the best cooperation path. The statistical population of the research was specialists, experts, and managers of companies providing financial services, among which 135 participants were selected as the statistical sample. According to the results, some of the paths of the cooperation model in financing were eliminated, and 24 paths remained out of 81 available options. Then, using the Stackelberg competition, the weights of each route were determined. Finally, with Stackelberg's competition calculations, the best cooperation path was determined, which included the guidance of financing management, the flexibility of financing service providers, the attraction of partners' support policies, and the allocation of financial resources based on the profit expansion prospect. Unlike most empirical studies of supply chain management, which use partners' data at the business unit or strategic partner level, in this research, game theory based on prospect theory was used to evaluate the cooperation strategy. The supply chain of financing services is created to solve financial problems, and different companies, according to the characteristics of their industry, adopt different cooperation strategies based on maximizing their profit in this chain of cooperation.